The Comparative Immunological Characteristics of SARS-CoV, MERS-CoV, and SARS-CoV-2 Coronavirus Infections - Zhang, Yun-yu; Li, Bi-ru; Ning, Bo-tao (Frontiers in Immunology, 2020)
Immune dysfunction and aberrant cytokine storms often lead to rapid exacerbation of the disease during late infection stages in SARS-CoV and MERS-CoV patients. However, the underlying immunopathology mechanisms are not fully understood, and there has been little progress in research regarding the development of vaccines, anti-viral drugs, and immunotherapy. The newly discovered SARS-CoV-2 (2019-nCoV) is responsible for the third coronavirus pandemic in the human population, and this virus exhibits enhanced pathogenicity and transmissibility. SARS-CoV-2 is highly genetically homologous to SARS-CoV, and infection may result in a similar clinical disease (COVID-19). In this review, we provide detailed knowledge of the pathogenesis and immunological characteristics of SARS and MERS, and we present recent findings regarding the clinical features and potential immunopathogenesis of COVID-19. Host immunological characteristics of these three infections are summarised and compared. We aim to provide insights and scientific evidence regarding the pathogenesis of COVID-19 and therapeutic strategies targeting this disease.